Work-Family Segmentation Preferences and Work-Family Conflict: Mediating Effect of Work-Related ICT Use at Home and the Multilevel Moderating Effect of Group Segmentation Norms - Yang, Jing; Zhang, Yucheng; Shen, Chuangang; Liu, Siqi; Zhang, Shanshan (Frontiers in Psychology, 2019)
Drawing on boundary theory, we propose a multilevel model that examines the effects of group segmentation norms on individual-level processes, relating segmentation preferences to work-family conflict via the use of a technological boundary. Data from 350 married employees in 81 working groups were used to test the model. The results of multilevel analysis revealed that work-related information and communication technology (ICT) use at home mediated the relationship between employee work-family segmentation preferences and work-family conflict, and the segmentation norms of the team moderated the relationship between work-family segmentation preferences and work-related ICT use at home. Managerial and practical implications are discussed.